Talking Stick Learning Model Assisted by Media Question Box: Effectiveness on Science Learning Outcomes in Elementary Schools - Purnama Sari, Bella Yulia; Candra Sayekti, Ika (Journal of Education Reseach and Evaluation, 2023)
Science learning is still conventional, causing students to be less focused and get grades in the low category. The research objective was to analyze the effectiveness of using the talking stick learning model assisted by the media questions box on science learning outcomes in elementary schools. This type of quantitative research with experimental design. Selection of the sample using simple random sampling. The research subjects were fifth-grade elementary school. The research design used the "One Group Pretest-Posttest Design" involving one group without a comparison group. Observation and test data collection techniques. Data analysis techniques using descriptive statistical analysis techniques and inferential statistical analysis. The results showed that after applying the talking stick learning method assisted by the questions box, it increased so that most student scores were in the high category. Based on the analysis results, the output of the Independent Sample T Test is known to be the value of Sig. (2-tailed) of 0.000, then H0 is accepted, so there is an average difference between the pretest and posttest results. The talking stick learning model assisted by the question box media effectively improves science learning outcomes for students. This research implies that teachers can apply learning models to develop learning outcomes and student activity in the classroom.